2010
DOI: 10.1063/1.3442486
|View full text |Cite
|
Sign up to set email alerts
|

Current transport and barrier height evaluation in Ni/InAlN/GaN Schottky diodes

Abstract: The current-voltage characteristics of the Ni/InAlN/GaN Schottky diodes were measured at various temperatures in the range of 300–700 K. The experimental data were analyzed considering different current-transport mechanisms. From the analysis it follows that the tunneling current, which might be due to a multistep tunneling along dislocations, is the dominant component at all temperatures in the samples investigated. The barrier height of the Ni/InAlN/GaN Schottky diodes, evaluated from the thermionic emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
18
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 11 publications
2
18
0
Order By: Relevance
“…The calculated values of Schottky barrier height and ideality factor were 0.84 eV and 1.51, respectively. Such barrier height obtained is close to the reported value of 0.75 eV measured by Arslan et al, 20 but significantly lower than 1.46 eV evaluated by Donoval et al 21 and 2.36 eV predicted for commonly used Ni contact on lattice-matched InAlN/GaN considering known work function of the metal and InAlN. 22 According to the reverse I-V curve, the device exhibits remarkably minimal gate diode reverse leakage current on the order of 1 and 40 lA/mm at gate-drain voltage of V GD ¼ À10 and À20 V, respectively.…”
Section: Resultssupporting
confidence: 90%
“…The calculated values of Schottky barrier height and ideality factor were 0.84 eV and 1.51, respectively. Such barrier height obtained is close to the reported value of 0.75 eV measured by Arslan et al, 20 but significantly lower than 1.46 eV evaluated by Donoval et al 21 and 2.36 eV predicted for commonly used Ni contact on lattice-matched InAlN/GaN considering known work function of the metal and InAlN. 22 According to the reverse I-V curve, the device exhibits remarkably minimal gate diode reverse leakage current on the order of 1 and 40 lA/mm at gate-drain voltage of V GD ¼ À10 and À20 V, respectively.…”
Section: Resultssupporting
confidence: 90%
“…15 The barrier height is 2.43 eV at 300 K and decreases slightly with increased temperature to reach 2.42 eV at 820 K. It should be mentioned that the room-temperature barrier height of ϳ1.46 eV has been reported for nonoxidized Ni/InAlN/GaN Schottky diodes. 11 This indicates an efficient enhancement of the barrier height by thermal oxidation of the InAlN surface. Temperature coefficient of the barrier height ␣ Х −2 meV/ 100 K is significantly smaller than would be expected according temperature dependence of the InAlN band gap.…”
mentioning
confidence: 90%
“…It should be noted, that the barrier height of ϳ1.46 eV was obtained on intentionally nonoxidized InAlN/GaN Schottky diodes using similar fitting analysis. 11,12 This indicates on high perspective of thermal oxidation procedure in order to enhance the Schottky barrier height on InAlN structures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is generally very high gate leakage current density of Schottky contacts under reverse bias, which is a severe problem hindering the applications of In x Al 1−x N / GaN HEMTs. 1,5,6 Arslan et al, 5 Chikhaoui et al, 6 and Donoval et al 7 analyzed the mechanisms of gate leakage current of Schottky contacts on In x Al 1−x N / GaN heterostructures. They suggested that the reverse-bias gate leakage current was dominated by Frenkel-Poole emission associated with dislocations in the In x Al 1−x N barrier.…”
mentioning
confidence: 99%